한,중,일 청소년의 식품소비 추이 비교분석 - 이계임; 주현정; 석교희미자; 이용선; 전형진 (농촌경제, 2009)
This study aims to provide implications for food consumption outlook by comparing and analyzing the food consumption of juveniles in Korea, China and Japan. The important results that were found from this study are as follows: The food consumption trend of Korean juveniles showed that rice consumption fell the fastest while the consumption of bread, cookies and pork, as well as eating outs, grew fast unlike any other age groups. In Japan, however, the decreasing consumption of rice has been slowing down since 2000. During this period, the consumption of pork has changed its course to an upward trend while the consumption of beef, fruits and vegetables has been falling. In the case of China, no significant changes were seen in the food consumption of juveniles in 2007 compared to 2002, and their food consumption was relatively low compared to other age groups. KCI Citation Count: 4